Peningkatan pengetahuan tentang energi terbarukan di Kampung Kwau: Improving Knowledge about Renewable Energy in Kwau Village - Rehiara, Adelhard Beni; Lesnussa, Henny A. B.; Likumahwa, Fervin M.; Marini, Sonya O.; Patiran, Abdul Z.; Stepanus, Jamius B.; Palintin , Antonius D.; Pasalli, Yulianus R.; Ismail, Saiful; Sarungallo, Pandung; Wihyawari, Bibiana R. (IGKOJEI: Jurnal Pengabdian Masyarakat, 2025)
ABSTRACT  The Community Service Program (PkM) is an annual initiative consistently conducted by the Faculty of Engineering at the University of Papua. In 2025, the program was carried out in Kampung Kwau, Warmare District, Manokwari Regency, West Papua Province, with the primary objective of enhancing local community understanding and skills in utilizing renewable energy, particularly through the use of energy-efficient solar lamps (LTSHE). The program began with presentations on the potential and benefits of renewable energy, followed by hands-on training in the maintenance and repair of LTSHE units. During the practical sessions, participants were introduced to techniques for replacing damaged batteries, cleaning solar panels, and understanding the basic operational system of the LTSHE devices. Despite challenges such as limited tools and varying levels of participant knowledge, the activity was met with enthusiastic responses. This program is expected to promote the sustainable use of environmentally friendly energy in Kampung Kwau.  Keywords: Renewable Energy; Kampung Kwau; LTSHE; Community Service; Solar Power.   ABSTRAK  Pengabdian kepada masyarakat (PkM) merupakan program tahunan yang secara konsisten dilaksanakan oleh Fakultas Teknik Universitas Papua. Pada tahun 2025, kegiatan ini berlokasi di Kampung Kwau, Distrik Warmare, Kabupaten Manokwari, Provinsi Papua Barat, dengan tujuan utama meningkatkan pemahaman dan keterampilan masyarakat dalam pemanfaatan energi terbarukan, khususnya melalui penggunaan lampu tenaga surya hemat energi (LTSHE). Rangkaian kegiatan diawali dengan penyampaian materi mengenai potensi dan manfaat energi terbarukan, kemudian dilanjutkan dengan pelatihan praktik pemeliharaan dan perbaikan LTSHE. Dalam sesi praktik, peserta diperkenalkan pada teknik penggantian baterai yang rusak, pembersihan panel surya, serta pemahaman dasar mengenai sistem kerja perangkat LTSHE. Meskipun terdapat kendala seperti keterbatasan alat dan variasi tingkat pemahaman peserta, kegiatan ini mendapat sambutan yang sangat positif. Program ini diharapkan dapat mendorong pemanfaatan energi ramah lingkungan secara berkelanjutan di Kampung Kwau dan menjadi model yang dapat direplikasi di wilayah lain. Kata kunci: Energi Terbarukan; Kampung Kwau; LTSHE; PkM; Tenaga Surya.